Analisis Plastisitas Fenotipe Kupu-Kupu Papilio ulysses Asal Papua - Euniche R.P.F. Ramandey; Evie L. Warikar (Jurusan Biologi FMIPA Universitas Cenderawasih, 2021)
Papua has a high diversity of butterflies, especially in mainland areas. Most of the data on the diversity and distribution of Papilionoidea, such as the example of Papilio ulysses in the mainland of Papua, are well known. Butterfly research in Papua is mostly aimed at species richness and abundance. Based on the results of specimen collection at the Papua Insect Collection Laboratory (KSP) Br Henk van Mastrigt FMIPA UNCEN, it can be seen that there are differences in morphological characters between P. ulysses in several areas in Papua, especially in the highlands and lowlands. The purpose of this study was to analyze the phenotypic plasticity pattern of P. ulysses stored in the KSP Laboratory. This research method is descriptive quantitative. The research sample consisted of 58 specimens with perfect wing shapes. The specimens were collected from Jayapura, Sarmi, Mamberamo, Timika, Pegunungan Bintang, Waropen and Biak-Supiori. The samples were documented using a digital camera and observed for wing variations using the Adobe Photoshop CS5 and Image J free program. Based on the observations, it shows that there are significant differences in the shape and size of P. ulysses that are found on the mainland and on islands. The morphology of butterflies originating from large areas is bigger than those of butterflies on islands. This butterfly plasticity process is a form of morphological adaptation to the surrounding environment. Key words: plasticity; P. ulysses; butterfly; Papua.